Human Assesment Peradilan Agama Pasca UU No. 3 Tahun 2006 - Muttaqien, Dadan (Al-Mawarid Jurnal Hukum Islam, 2007)
Islam denotes religion that regulates the relation between Allah and humankind, this called rituals or ibadah mahdah. Besides, it also teaches that of interhumankind relationship that named social matters relationship or muâamalah. Either ibadah mahdah or muâamalah Islamic law constitutes Allahâs blessing for human. Islamic law on muâamalah in Indonesia develops in accordance with entering Islam in Indonesia until after Indonesian independence. And Islamic law on muâamalah becomes one of Indonesian living law. Enforcing Islamic Law in Indonesia needs the institution of court thatis the religious, and in this moment it is regulatedaccording to article 10 verses (1) and (2) of Act No.4 year 2004. Kata kunci: Peradilan agama, ekonomi Syariâah, Indonesia, SDM dan prodi Syariâah.